Analysis of Perceived Physical and Motor Competence in 10- to 13-year-old Spanish Children - Pedro Gil-Madrona; Antonio Pita-Lozano; Arturo Díaz-Suárez; Guillermo Felipe López Sánchez (Desafio Singular, 2018)
It was our objective to analyze the perceived physical and motor competence in 10- to 13-year-old Spanish children, and to validate to the Spanish language and context the questionnaire of Scrabis-Fletcher and Silverman (2010). The perception of competence was analysed in 27 schools of Albacete (Spain), with a total of 389 boys and 391 girls, whose age ranged from 10 to 13 (average=11.08 and SD=0.43). Different analyses were performed, starting with a forward analysis of the items, using graphics and statistics. After this, an internal consistence study was performed, through Cronbach's alpha, using a multilevel package, version 2.3. Finally, the constructs structure was analyzed through a factorial confirmatory analysis (FCA), which used a Lavaan package, version 0.5-11. The consistence was high as a whole (Cronbach's alpha: 0.74). There was a high correlation between all items, even those from different factors. Regarding the analysis of students´ perceived physical and motor competence, the best values were obtained in the perceptions they had about their teachers and classmates, although they had worse values about their own personal experiences. Two questionnaires of 2 and 3 factors, using 7 and 14 items, respectively were established. Therefore, the instrument Perception of Competence in Middle School Physical Education was validated within the Spanish social context. The main practical application is the possibility of using this questionnaire in the PE lessons in Spain to know and increase the perceived physical and motor competence of the children.